2018
DOI: 10.1038/s42003-018-0017-7
|View full text |Cite|
|
Sign up to set email alerts
|

The EphA2 receptor is activated through induction of distinct, ligand-dependent oligomeric structures

Abstract: The EphA2 receptor tyrosine kinase is capable of activating multiple diverse signaling pathways with roles in processes such as tissue homeostasis and cancer. EphA2 is known to form activated oligomers in the presence of ephrin-A ligands. Here, we characterize the lateral interactions between full-length EphA2 molecules in the plasma membrane in the presence of three types of ligands (dimeric ephrinA1-Fc, monomeric ephrinA1, and an engineered peptide ligand) as well as in the absence of ligand, using a quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 62 publications
11
91
0
Order By: Relevance
“…To accomplish this, we first employed Fluorescence-Lifetime Imaging Microscopy for Forster Resonance Energy Transfer (FLIM-FRET). FRET based imaging capitalizes on close proximity of two proteins to visualize protein-protein interactions, including receptor dimerization and receptor-ligand complex formation [60]. FLIM characterizes the duration of a fluorophore’s excited state before returning to the ground state.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish this, we first employed Fluorescence-Lifetime Imaging Microscopy for Forster Resonance Energy Transfer (FLIM-FRET). FRET based imaging capitalizes on close proximity of two proteins to visualize protein-protein interactions, including receptor dimerization and receptor-ligand complex formation [60]. FLIM characterizes the duration of a fluorophore’s excited state before returning to the ground state.…”
Section: Resultsmentioning
confidence: 99%
“…Using a quantitative FRET approach in live cells, we have previously shown that in HEK293 cells transiently transfected with EphA2, the receptor weakly dimerizes in the absence of a bound ligand (22) through an extracellular interface known as the "clustering" interface (19,20). Furthermore, we found that the YSA-GSGSK (3) peptide increases the formation of these EphA2 unliganded dimers (23,24). In contrast, the monomeric , total EphA2 levels, and AKT phosphorylation on Ser 473 (pAKT, indicative of AKT activation).…”
Section: Nanomolar Peptides That Activate or Inhibit Epha2 Signaling mentioning
confidence: 93%
“…In these experiments, FRET was measured in 300 -400 individual cells with different EphA2 expression levels. FRET efficiency, EphA2-mTURQ (donor) concentration, and EphA2-EYFP (acceptor) concentration in the plasma membrane were measured in micrometer-sized regions of the plasma membrane as described (23), and the data derived from the individual cells were combined to yield binding curves. A least-square error analysis of the FRET data, performed as described previously (25), showed that these data are best described by a monomer-dimer association model rather than a higher-order association model.…”
Section: Nanomolar Peptides That Activate or Inhibit Epha2 Signalingmentioning
confidence: 99%
“…Upon binding to their ligands, they often oligomerize and crossphosphorylate each other, especially on tyrosine residues at the critical juxtamembrane domain and at the activation loop (49-51) to transduce various cellular signals. In the case of the EPH receptors, many of which are upregulated in numerous cancers, ligand activation leads to inhibition of tumor growth, migration and invasiveness (51). In our study when SCC cells were treated with EphrinA1 the natural ligand of EPHA2 (non-tumorigenic signaling) in in vitro culture, we did not see an inhibition in cellular proliferation of LSCC and HNSCC cells underscoring the need to study the presence of other degenerate unexplored pathways regulating EPHA2 signaling.…”
Section: Discussionmentioning
confidence: 49%